2021
DOI: 10.1128/mbio.02696-20
|View full text |Cite
|
Sign up to set email alerts
|

Carboxysome Mispositioning Alters Growth, Morphology, and Rubisco Level of the Cyanobacterium Synechococcus elongatus PCC 7942

Abstract: Photosynthetic cyanobacteria are responsible for almost half of global CO 2 fixation. Due to eutrophication, rising temperatures, and increasing atmospheric CO 2 concentrations, cyanobacteria have gained notoriety for their ability to form massive blooms in both freshwater and marine ecosystems across the globe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 76 publications
(100 reference statements)
2
9
0
Order By: Relevance
“…Overall, McdA mutant strains predicted to be defective for ATP-binding and dimerization displayed a cell elongation phenotype, and possessed few and irregularly-spaced carboxysome aggregates. These phenotypes match what we have previously observed in the mcdA deletion strain (Rillema et al, 2021), which suggests a complete loss of function in carboxysome positioning when McdA cannot bind ATP and dimerize.…”
Section: Strategy For Trapping and Imaging Mcda At Specific Steps Of Its Atpase Cyclesupporting
confidence: 89%
See 3 more Smart Citations
“…Overall, McdA mutant strains predicted to be defective for ATP-binding and dimerization displayed a cell elongation phenotype, and possessed few and irregularly-spaced carboxysome aggregates. These phenotypes match what we have previously observed in the mcdA deletion strain (Rillema et al, 2021), which suggests a complete loss of function in carboxysome positioning when McdA cannot bind ATP and dimerize.…”
Section: Strategy For Trapping and Imaging Mcda At Specific Steps Of Its Atpase Cyclesupporting
confidence: 89%
“…Heterotrophic bacteria have been shown to undergo cell elongation as a carbon-limitation response (Rangarajan et al, 2020). We also recently proposed that carboxysome aggregation results in decreased carbon-fixation efficiency, and that cell elongation is a response triggered by the resulting carbon limitation in this photoautotroph (Rillema et al, 2021). Since the phenotype of these predicted McdA trap mutants mirror the mcdA deletion strain, our findings suggest a complete loss of function in carboxysome positioning when McdA cannot bind ATP, dimerize, and adopt its nucleoid-binding conformation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it is attractive to speculate that coating carboxysomes with a viscous, pH-sensitive McdB phase may influence the diffusivity of carboxysome shells to protons, which is an important aspect of current models for an efficient CCM (68, 69). Indeed, in a previous study, we have shown that cells deleted for McdB show additional growth deficits compared to cells lacking McdA, suggesting that McdB plays additional roles in the CCM beyond spatially regulating carboxysomes with McdA (71). Moreover, a separate study has shown that the shells of purified carboxysomes, which lack McdB, are freely permeable to protons (72).…”
Section: Discussionmentioning
confidence: 95%